Optimizing high-frequency and low-frequency deep brain stimulation parameters for drug-resistant epilepsy: Mechanisms, clinical outcomes, and future directions - Faeze Sadat Ahmadi Tabatabaei; Mohammad Taghi Joghataei; Kiana Askarian; Leila Riahi Pour; Bita Kouhnavard Pour; Nooshin Ahmadirad (Interdisciplinary Neurosurgery)
Objective: This review evaluates the therapeutic potential of high-frequency stimulation (HFS) and low-frequency stimulation (LFS) in deep brain stimulation (DBS) for drug-resistant epilepsy (DRE), focusing on mechanisms, target selection, and parameter optimization. Methods: A synthesis of preclinical and clinical studies was conducted, analyzing electrode placement, stimulation parameters (frequency, pulse width, intensity), and outcomes across key DBS targets, including the centromedian thalamus, anterior thalamus, and hippocampus. Emerging non-invasive neuromodulation strategies, such as repetitive transcranial magnetic stimulation (rTMS), were contextualized within the broader therapeutic landscape. Results: HFS (100–130 Hz) demonstrates robust antiepileptic effects by disrupting cortical synchronization and enhancing GABAergic inhibition, achieving sustained seizure reduction in 40–60 % of DRE patients. LFS 1–10 Hz shows variable efficacy, with risks of exacerbating seizures via cortical synchronization. Optimal pulse widths (60–240 μs) and amplitude (150–300 μA) require patient-specific calibration. rTMS (0.3–1 Hz) exhibits adjunctive potential for non-invasive modulation of epileptogenic networks, particularly when combined with neuroimaging. Conclusion: While DBS remains a cornerstone for DRE, parameter optimization is critical to balancing efficacy and safety. Future research should prioritize closed-loop systems, biomarker-driven protocols, and synergies between invasive (DBS) and non-invasive (rTMS) neuromodulation.